2001
DOI: 10.1177/0263211x010293007
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring Role of the Academic Middle Manager in Secondary Schools

Abstract: This article examines aspects of the monitoring role of academic middle managers insecondary schools since the implementation of the Education Reform Act of 1988,drawing on the perceptions of middle managers. The data were collected from a largescalepostal survey of middle managers in three local authorities and three case-studyschools. Middle managers acknowledge the need for management tasks, including themonitoring of colleagues teaching, to be part of their role but still experience difficultiesin fulfilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 3 publications
0
53
0
2
Order By: Relevance
“…Coupled by being also referred to as teachers and hence people whose possible avenues of social influence in their departments are then rooted in a seemingly inconsistent work role where the incumbent is both superior and professional colleague (Paulsen, 2008;Jones & Duckett, 2006), academic middle managers can best be understood in two context, i.e., the school wide context and department context (Wise, 2001). In the school wide context, by virtue of their position in the school hierarchy, middle managers are seen as operating at the interface between different levels and different sources of influence and change with their role shifting towards managerialism in which the middle managers find themselves managing the intersection of traditional and new organisational cultures and trying to exert school-wide influence (Wise, 2001;Hancook & Hellawell, 2003).…”
Section: Role Autonomymentioning
confidence: 99%
See 3 more Smart Citations
“…Coupled by being also referred to as teachers and hence people whose possible avenues of social influence in their departments are then rooted in a seemingly inconsistent work role where the incumbent is both superior and professional colleague (Paulsen, 2008;Jones & Duckett, 2006), academic middle managers can best be understood in two context, i.e., the school wide context and department context (Wise, 2001). In the school wide context, by virtue of their position in the school hierarchy, middle managers are seen as operating at the interface between different levels and different sources of influence and change with their role shifting towards managerialism in which the middle managers find themselves managing the intersection of traditional and new organisational cultures and trying to exert school-wide influence (Wise, 2001;Hancook & Hellawell, 2003).…”
Section: Role Autonomymentioning
confidence: 99%
“…In the school wide context, by virtue of their position in the school hierarchy, middle managers are seen as operating at the interface between different levels and different sources of influence and change with their role shifting towards managerialism in which the middle managers find themselves managing the intersection of traditional and new organisational cultures and trying to exert school-wide influence (Wise, 2001;Hancook & Hellawell, 2003). In the department context, middle managers are tasked with ensuring good teaching and learning, a role that has traditionally been recognised as at the heart of the middle manager's work and which comes with the inherent problems of the monitoring and collegiality duality Wise, 2001). As a result of this role conflict and role ambiguity, tensions are therefore frequently observed that characterise this duality in the work role of the academic middle manager Wise, 2001).…”
Section: Role Autonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Two significant tensions affecting subject leaders are first, 'between expectations that [the] role had a whole school focus and their loyalty to their department, and second, between a growing school culture of line management within a hierarchical framework and a professional rhetoric of collegiality' (Bennett et al, 2007). The monitoring of colleagues' work and passing on assessments to more senior colleagues are an example of a situation in which these tensions can emerge (Glover et al, 1998) as classroom observation by middle leaders has been seen by many departmental members as demonstrating a failure of trust and an implementation of a culture of surveillance (Wise, 2001). …”
Section: Background Of Secondary Schools and Middle Leaders In Englandmentioning
confidence: 99%